Experience of transformative leadership: Subordinate's perspective - Jolanta Sondaitė; Greta Keidonaitė (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Despite the growing popularity of transformational leadership (TL) in organization studies, there is a lack of studies trying to reveal subordinate's perspective on experience of TL. The present study examined how subordinates employed in customer service experience TL during organizational change. The participants were people working in two international organizations operating in Lithuania. The data were collected through semi-structured interview. Phenomenological procedures were used to analyze the data. The conducted phenomenological analysis of TL from the subordinate's perspective reveals that subordinates under TL feel secure and empowered, have extensive data about the ongoing change, receive full manager's support and individual attention, share acquired knowledge in performing delegated duties and collectively aspire for a common generally accepted goal set by the manager and consequently are more positive about organizational change. The results of the present study contribute to the better understanding of the inner experiences of TL by subordinates working as customer service specialists in the context of organizational changes.
Keywords: M12; 650; transformational leadership; subordinate; experience; manager; qualitative study; phenomenological analysis